2013
DOI: 10.1016/s2213-2600(13)70119-x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the sensitivity and specificity of Xpert MTB/RIF assay as an early sputum biomarker of response to tuberculosis treatment

Abstract: Global Alliance for TB Drug Development, Bill & Melinda Gates Foundation, UK Medical Research Council, German Ministry of Science and Technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
127
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 172 publications
(140 citation statements)
references
References 26 publications
9
127
0
4
Order By: Relevance
“…The close comparability between MBL and culture contrasts with data for treatment monitoring using the GeneXpert MTB/RIF assay (Xpert; Cepheid, CA, USA). GeneXpert MTB/RIF did not respond to changes in bacterial load as rapidly as did culture (17). Within-subject variation of Xpert was high, at 56.7%.…”
mentioning
confidence: 79%
“…The close comparability between MBL and culture contrasts with data for treatment monitoring using the GeneXpert MTB/RIF assay (Xpert; Cepheid, CA, USA). GeneXpert MTB/RIF did not respond to changes in bacterial load as rapidly as did culture (17). Within-subject variation of Xpert was high, at 56.7%.…”
mentioning
confidence: 79%
“…NanoDisk-MS also was able to precisely quantify serum antigen concentrations, a highly desirable feature for monitoring responses to anti-TB therapy, given that assays currently used to monitor treatment response provide only qualitative or semiquantitative results (smear and culture) or exhibit significant latency (Xpert). A study evaluating serial sputum samples from patients with smear-positive TB found that assay positivity and grade decreased linearly starting at ∼2 wk (smear), 4 wk (culture), or 6 wk (Xpert) posttreatment (37). CD4 + T-cell responses also have been reported to differentiate LTBI and active TB cases and to monitor treatment responses, although only HIV-negative and culture-and/or smear-positive PTB patients were analyzed using this labor-intensive method, so that its clinical utility remains unclear (38).…”
Section: Discussionmentioning
confidence: 99%
“…This may have to some extent contributed to further lowering the yield of culture compared to Xpert. As the excretion of residual persistent DNA from dead organisms has been suggested as a reason for positive Xpert but negative smear and/or culture results on samples taken during and at the end of treatment, 18 a positive Xpert result in recently treated TB patients should be correlated with the clinical condition of the patient, and should ideally be confirmed by culture, although in GS the culture yield is known to be low.…”
Section: Discussionmentioning
confidence: 99%